Detection of polysaccharides from local algae in fresh water - Al-Rikabi, Nawras; Roa’a Jaafar Khairallah (University of Thi-Qar Journal of Science, 2025)
-The research focused on identifying the polysaccharide composition of Cladophora algae species collected from the Tigris River for carrageenan, agar and alginate analysis. The biochemical diversity of Cladophora green algae was demonstrated through the discovery of compounds traditionally linked to red and brown marine algae. HPLC analysis provided detailed information about polysaccharide distribution through its measurement of polysaccharide content. The analysis of Cladophora revealed that carrageenan and agar existed at 1.21% and 1.25% levels while alginate reached 1.46%. The discovery of carrageenan in green algae contradicts the common belief that this substance exists only within rhodophyta species. The polysaccharide synthesis and accumulation process in the Tigris River appears to be influenced by the river’s unique freshwater environment together with its low salinity and fluctuating nutrient levels and seasonal temperature changes. The main polysaccharide identified in the sample was agar which suggested conserved biosynthetic pathways and alginate presented industrial value despite its minimal concentration. The two unknown polysaccharide peaks at positions 3 and 10 played a crucial role in establishing the biochemical profile of the sample. The research shows how environmental conditions together with methodological approaches affect polysaccharide production. The minimal amounts of carrageenan, agar and alginate suggest that Cladophora could serve as a supplementary resource instead of the primary one. The discovery of different unknown polysaccharides creates new research opportunities for industry to explore potential new compounds.